PERANCANGAN BUSINEES MODEL CANVAS DAN BLUE OCEAN STRATEGY UNTUK SCALE UP USAHA PENGRAJIN ALAS KAKI SOOKO MOJOKERTO - Sujani, Sujani; Arif, Mochamad Syaiful (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
The small footwear industry is a commodity that residents in Sooko, Mojokerto, can rely on. Affected by Covid-19, since May 2020 exports have had a significant effect on business continuity, while the local market was felt at the end of March. Buyers tended to cancel their orders and many craftsmen's businesses were closed. The canvas business model is an instrument in creating new businesses. To deal with new market situations, the blue ocean strategy is chosen then. In producing the BMC formula, several changes are made to: customer relationship in endorsement; stalls on the Channel; Key Activities in online sales and digital marketing as well as patent rights. Revenue Streams on product usage fees and licensing, then focusing on direct selling and indirect selling. Scale-up of efforts carried out in production & digital marketing collaboration. Increasing in brand & design patents and also sales platforms. The highest scale value is branding.